Analysis of differences in intesity and movement quantity between guard and wing during the water polo game - Lozovina, M. (Research in Kinesiology, 2017)
On the sample of 320 water polo quarters, as entities in this investigation, 21 variables were performed and 8 derived vari-ables were used in this research. Data processing methods have been brought into accord with the aims of this research. Basic statisti-cal parameters as well as distribution of all the measured and derived variables have been calculated. The aim of this investigation was to confirm is the structure of the movement in the vertical and horizontal phase in a water polo, intensity, frequencies and time as equivalent for effort for two different positions (guard and wing) really different. Basic statistics was performed on z-scores, as well as analysis of variance (ANOVA) and F-test differences between the guard and the wing. Discriminate analysis was also performed and structure discriminate function was calculated. The results show: it is possible to register and define differences in the roles guard and wing in water polo that confirms the first hypothesis in this research. The guard position defines and discriminates of the wing: frequencies of duels and time spent in duels during the game. Conclusion is that quad position defines high level of work intensity in the vertical stage (phase) of the game through over maximal stress (duels). This is also the confirmation of the second hypothesis in this paper. The wing is defined, and it is different from the guard in: frequency of playing with an uneven number of players (player less / more), the frequency of action, and the time spent in the game with an uneven number of players and the total time spent in the game. That confirms the third hypothesis in this research. What makes the wing and guard no different are frequencies of action, over-all swimming meters and frequencies of slowly swimming. Results of this research provide theoretical explanation of this less covered field in top sports, as well in water polo, and will be a base for the practice of water polo trainers in real work with centers and wings.